TELAAH FILOSOFIS ATAS PENDIDIKAN KARAKTER DI ERA MILENIAL - Utang, Herman Yosep (Pastoralia Jurnal Penelitian Dosen, 2021)
Self-consciousness that is manifested in the way of life and how to behave is an ontological order that should be the basis for human character education in every era, including in this millennial era. Humans educate themselves based on the context of space and timewhich always changing so that they live and realize their way of being in harmony with the times. There is a problem of correlation, coherence between self-consciousness and way of life. Character education becomes a way of life and the fruit of a renewed awareness. Therefore, the character education should become a calling and a mission, a gift and a responsibility that never ends.